Collecting behavioural data across countries during pandemics: Development of the COVID-19 Risk Assessment Tool - Peters, Gjalt-Jorn; Kwasnicka, Dominika; Ten Hoor, Gill A.; Crutzen, Rik; Varol, Tugce; Warner, Lisa Marie; Algargoosh, Mahdi; Ali, Eskinder Eshetu; Anwar, Mudassir; Asih, Sali Rahadi; Baltas, Zuhal Feryal; Berry, Emma; et al. (Springer Science and Business Media LLC, 2025)
Abstract Tools that can be used to collect behavioural data during pandemics are needed to inform policy and practice. The objective of this project was to develop the Your COVID-19 Risk tool in response to the global spread of COVID-19, aiming to promote health behaviour change. We developed an online resource based on key behavioural evidence-based risk factors related to contracting and spreading COVID-19. This tool allows for assessing risk and provides instant support to protect individuals from infection. The Risk Estimation Questions assessed users’ location, age, gender, work environment, day-to-day behaviours currently performed, and conditions under which these behaviours would change. Users were also asked to estimate how often they keep their distance from others in public and regularly wash their hands, and the procedures they follow to do so. A multidisciplinary research team of more than 150 international experts developed the tool. Over 60,000 users in more than 150 countries have assessed their risk and provided data. The majority of respondents reported that they almost always keep their distance from others in public places, and most participants reported washing their hands after touching public or shared surfaces or when entering buildings. The tool, data, and results were openly shared to support government and health agencies developing behaviour change interventions. This tool creates a blueprint for similar digital infrastructure that can be replicated and used in future pandemics.
Keywords: Male; Adult; Risk; Angewandte Psychologie; COVID-19/prevention & control; Health Behavior; Experimental and Cognitive Psychology; Original Manuscript; Health behaviour change; Risk Assessment; Data Collection/methods; Arts and Humanities (miscellaneous); SDG 3 - Good Health and Well-being; Applied psychology; Developmental and Educational Psychology; Psychology; Humans; Risk Assessment/methods; Psychology(all); Pandemics; SARS-CoV-2; Data Collection; People; Systems; COVID-19; Science; Middle Aged; Social psychology; Impact; Female; Psychology (miscellaneous); Strategies; Covid-19